Evaluation of whip use and prevalence in elite and non-elite show jumpers. - Watkins, C.; Murphy, D. (Embracing science to enhance equine welfare and horse-human interactions, 2013)
The use of the whip and concern with equine welfare in the racing industry has filtered through to other equestrian disciplines; however, as yet, whip use has not been investigated in Show Jumping (SJ). Therefore the aims of this research were to establish whether a correlation exists between occurrence of whip use and performance, and whether this differs between competition levels. Direct observations of whip carriage, use, and rein release were made of n=229 non-elite (NE) (0.9-1.15m) and n= 229 elite (E) (1.2m +) at affiliated SJ competitions. NE riders had a higher prevalence of whip carriage (69%) compared with E riders (62%). Faults were 1.3 times more likely (p=0.0111) to occur if a whip was carried. A clear round was achieved by 22.7% of competitors who carried but did not use a whip, followed by non-carriers (15.7%) and whip users (7.4%). NE riders were more likely to use the whip (p=0.0002) and more likely to remove their hand from the rein (p=0.008). Data indicates that likelihood of faults increases with increased occurrence of whip use and suggests that British SJ could afford to review their whip rules to avoid unnecessary whip use in line with updated racing regulations. Education and training of riders is paramount to ensure NE riders do not overuse the whip and potentially implicate their horse`s welfare. Further research could incorporate rider`s perception of correct use and determine factors explaining why carrying a whip but not using it resulted in the most clear rounds to inform rule development and training techniques. Layperson`s paragraph: Whip use is prevalent in show jumping and this research shows that Increase use of the whip does not mean an increased chance of completing a successful clear round. The prevalence of whip use is higher in lower level competitors. BS rule currently do not protect horses from whip over use as currently written.